Complete mitochondrial genome of Atergatis integerrimus (Decapoda, Xanthidae) from the Philippines. Issue 1 (2nd January 2018) - Karagozlu, Mustafa Zafer; Barbon, Michelle M.; Dinh, Thinh Do; Demayo, Cesar G.; Kim, Chang-Bae
Abstract: In this study, a complete mitochondrial genome from the red egg crab, Atergatis integerrimus was sequenced and analyzed. The mitochondrial genome length is 16, 333 bp and is composed of 13 protein-coding, two ribosomal RNA and 22 tRNA genes. The structure and gene orientation of the mitochondrial genome was found to be identical with the other brachyurans. The position of A. intergerrimus in the superfamily Xanthoidea was determined based on the mitochondrial protein-coding genes. The result of the phylogenetic relationship study showed that A. integerrimus was closest to Leptodius sanguineus.